Changing returns-to-scale and deepening of factor-endowments-induced specialization: Exploring broader linkage between agricultural mechanization and agricultural transformation in Nepal - Takeshima, Hiroyuki; Kumar, Anjani (International Food Policy Research Institute, 2020)
Heterogeneity in factor endowments and the degree of specializations induced by comparative advantages are among the crucial factors that affect the overall productivity of the economy. Few studies, however, investigate what strengthens such endowment-related specialization patterns in the agricultural sector in low-income countries, although such evolutions have profound effects on the role of factor endowments in households’ behaviors. This is in contrast to well-established international trade theory, such as the Heckscher–Ohlin theorem which describes how heterogeneity in endowment across countries gives rise to comparative advantages for specialization and trade. We partly fill this critical knowledge gap by providing a set of evidence from Nepal, which is a country that has historically been dominated by smallholder farmers and yet has recently been experiencing rapid structural transformation within the agricultural sector. Specifically, we show the following: the agricultural sector in Nepal has experienced a significant increase in returns-to-scale (RTS) in production in recent years during the process of growing adoptions of agricultural mechanization through the custom-hiring market. Such increase in RTS has primarily strengthened the linkages between factor endowment heterogeneity (across farm households) and their specialization behaviors in labor, land, and the agricultural capital market. Both cross-section and panel-data of households in Nepal extracted from Nepal Living Standards Surveys are used to generate this evidence. We find that rising RTS associated primarily with tractor use growth has been inducing greater exploitations of comparative advantages; agricultural households have been increasingly specializing in exchanges of production factors, services, and outputs, in ways consistent with predictions based on their relative factor endowments. Specifically, the rise in RTS has induced households with more labor, land, and capital endowments to rent out their labor, land, and credit, respectively, within the agricultural sector, while increasingly renting-in the other factors with which they are less endowed. The results suggest that understanding factor endowments heterogeneity among agricultural households is becoming increasingly important for effective agricultural policy designs in countries like Nepal, where employment shares in the agricultural sector remain high despite the growth in mechanization.